Failure of Healthcare Provision for Attention-Deficit/Hyperactivity Disorder in the United Kingdom: A Consensus Statement - Young, Susan; Asherson, Philip; Lloyd, Tony; Absoud, Michael; Arif, Muhammad; Colley, William Andrew; Cortese, Samuele; Cubbin, Sally; Doyle, Nancy; Morua, Susan Dunn; Ferreira-Lay, Philip; Gudjonsson, Gisli; et al. (Frontiers in Psychiatry, 2021)
Background: Despite evidence-based national guidelines for ADHD in the United Kingdom (UK), ADHD is under-identified, under-diagnosed and under-treated. Many seeking help for ADHD face prejudice, long waiting lists, and patchy or unavailable services, and are turning to service-user support groups and/or private healthcare for help. Methods: A group of UK experts representing clinical and healthcare providers from public and private healthcare, academia, ADHD patient groups, educational and occupational specialists, met to discuss shortfalls in ADHD service provision in the UK. Discussions explored causes of under-diagnosis, examined biases operating across referral, diagnosis and treatment, together with recommendations for resolving these matters. Results: Cultural and structural barriers operate at all levels of the healthcare system, resulting in a de-prioritisation of ADHD. Services for ADHD are insufficient in many regions, and problems with service provision have intensified as a result of the response to the COVID-19 pandemic. Research has established a range of adverse outcomes of untreated ADHD, and associated long-term personal, social, health and economic costs are high. The consensus group called for training of professionals who come into contact with people with ADHD, increased funding, commissioning and monitoring to improve service provision, and streamlined communication between health services to support better outcomes for people with ADHD. Conclusions: Evidence-based national clinical guidelines for ADHD are not being met. People with ADHD should have access to healthcare free from discrimination, and in line with their legal rights. UK Governments and clinical and regulatory bodies must act urgently on this important public health issue.